Pengaruh Desain dan Citra Merek terhadap Keputusan Pembelian Produk Body & Soul di Kabupaten Badung - Sriani, Ni Nyoman; Ayu Wimba, I Gusti; Wina Premayani, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study was to find out how the influence of design and brand image on purchasing decisions. This research was conducted in Body and Soul, Badung Regency. The number of samples taken was 100 respondents. Data collection techniques are observation, interviews, documentation, literature, and questionnaires. While the data analysis techniques are validity, reliability, classic assumption test, multiple regression analysis, correlation, determination, t-test and f-test. The test results show that there is a positive and significant influence between the design and the purchase decision, which means that the higher the design, the higher the purchase decision. There is a positive and significant influence between brandimage and purchase decision, which means that the higher the brand image, the higher the purchase decision. There is a positive and significant influence between design and brand image on purchasing decisions, which means that the higher the design and brand image, the higher the purchasing decision.